Mashup Technology: Beyond Open Programming Interfaces. - Han, Hao; Xue, Yinxing; Oyama, Keizo (Computer (00189162), 2013)
Web application integration at the presentation and logic layers is an appealing approach to enhancing Web services technologies. However, it's certainly not without challenges.